Erratum: Ultrasonographic aspects of the gallbladder mucocele in 30 dogs: retrospective study - Fernanda de Carlo Deusdado; Carla Aparecida Batista Lorigados; Marianna Pantano; Ayne Murata Hayashi; Fabio Calderon (Brazilian Journal of Veterinary Research and Animal Science, 2023)
Gallbladder mucocele is characterized by hyperplasia of the gallbladder epithelium, increased mucus production, accumulation, and densification of the bile content, which can lead to biliary obstruction, necrosis, and rupture of the gallbladder wall. Its finding may be accidental or related to symptoms. A retrospective study (2016-2019) was carried out based on abdominal ultrasound examinations in dogs, correlating aspects of the gallbladder and biliary system in the mucocele with existing comorbidities. Thirty dogs diagnosed with biliary mucocele were evaluated, of which 46.66% had the disease at an early stage, and 53.33% showed a more advanced stage. Of these, 66.66% were related to endocrinopathies and hyperadrenocorticism. Signs of extrahepatic bile duct obstruction and biliary peritonitis were observed in two animals. Due to their potential risk of complications, follow-up ultrasound assessments are indicated in cases that opt for clinical treatment, not excluding the need for surgical intervention.